Clinical Results of Carotid Artery Stenting (CAS) in Patients over 80 Years Old: Strategy and Usefulness of Tailored-CAS Algorithm Based on Lesion Morphology and Plaque Characteristics - MATSUMOTO, Hiroyuki; TETSUO, Yoshiaki; TAKEMOTO, Hideki; NAKAO, Naoyuki; NISHIYAMA, Hirokazu (Nōshotchū no geka, 2019)
Purpose: Carotid artery stenting (CAS) reduces the risk of ischemic stroke in patients with carotid artery stenosis, although recent randomized trials showed an increase in periprocedural stroke risk in elderly patients undergoing CAS. Recently, the safety and efficacy of tailored-CAS was reported. We retrospectively compared the clinical results of tailored-CAS between patients >80 and <80 years old.Materials and methods: From April 2013 to December 2016, 18 of 105 patients who underwent tailored-CAS at our hospital were ≥80 years old. The patients were examined by computed tomography angiography, magnetic resonance angiography, magnetic resonance imaging - black blood imaging, ultrasonography, and angiography before the procedure. The choice of embolus prevention procedure and stent type depended on lesion morphology and plaque characteristics. We analyzed the 30-day stroke risk, death rates, and diffusion-weighted imaging (DWI) positive rates between ≥80- and <80-year-old patients.Results: The periprocedural stroke rate was 3.4% (3/87) in <80-year-old patients and 5.6% (1/18) in ≥80-year-old (p = 0.17). The incidence of new DWI lesions after CAS was 34/87 (39%) in <80-year-old patients, and 4/18 (22.2%) in ≥80-year-old patients (p = 0.67). No significant differences were observed between the two groups regarding periprocedural events and DWI-positive rates.Conclusion: The tailored-CAS algorithm for selecting the most appropriate embolic protection device and stent, which is based on lesion morphology and plaque characteristics, may be useful in elderly patients with carotid stenosis.